PENINGKATAN KREATIFITAS PEMBUATAN “SANDHAL” DARI LIMBAH PERCA BATIK PADA IBU-IBU GURU “SLB B YRTRW” DI GILINGAN, BANJARSARI, SURAKARTA - Nuryati; Hariyanti (STIE St. Pignatelli Surakarta, 2021)
Community service is one of the duties of a lecturer from the Tri Dharma College. As an effort to help the community, the PkM Team from STIE-AUB Surakarta held training on making sandals from batik patchwork for teachers at SLB B YRTRW Gilingan, Banjarsari, Surakarta, with the hope that later it could be passed on to their students. SLB B YRTRW is an extraordinary school that educates deaf and speech-impaired children, so that with this training they are able to have the skills to make sandals from batik patchwork, so that if they are practiced well, income will come automatically. At this SLB B RTRW school, there has never been any training in making sandals from patchwork of batik cloth, so this training is very useful for teachers and especially students in the future. The activity has been carried out at SLB B YRTRW Jl. Gumunggung Rt 01//II Gilingan, Banjarsari Surakarta with the target of SLB B teachers on October 21, 2020, which was attended by 15 participants, because during the pandemic, there were not many participants. The method of making this sandal product is with lectures, and direct practice of making sandals. As a result of this service, teachers benefit from knowledge and skills in making sandals from batik patchwork, and in the future they can be transferred to students, so that even though they are not perfect, they are also able to have skills like ordinary/normal people.